PAPERLESS OFFICE SEBUAH KEBUTUHAN KANTOR MASA DEPAN DI INDONESIA - Barnad Barnad (Politeknik Ubaya, 2019)
The development of computer technology and information and communication technology has entered all aspects of life both personally and business institutions such as offices. Work behavior patterns that still apply traditional offices with modern office equipment only produce work effectiveness, but have not produced work efficiency. In this paper, we will describe the results of traditional work behavior patterns, especially the use of wasteful paper, and how to make the most of information technology that has been owned to change traditional behavior patterns into modern ones which will result in a maximum reduction in paper use. Thus the achievement of work productivity is not only in the form of work effectiveness, but work efficiency can be achieved by applying modern work behavior. This change in work behavior indirectly plays a role in helping to improve the environment, because each sheet of paper used is the result of logging as the main ingredient. The application of modern work behavior patterns will have a significant impact if carried out jointly and thoroughly at each office.